2019
DOI: 10.1088/1748-3190/aaffa4
|View full text |Cite
|
Sign up to set email alerts
|

A bio-inspired sighted robot chases like a hoverfly

Abstract: Here we present a novel bio-inspired visual processing system, which enables a robot to locate and follow a target, using an artificial compound eye called CurvACE. This visual sensor actively scanned the environment at an imposed frequency (50Hz) with an angular scanning amplitude of 4.2 • and succeeded in locating a textured cylindrical target with hyperacuity, i.e. much finer resolution than the coarse inter-receptor angle of the compound eye. Equipped with this small, lightweight visual scanning sensor, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 53 publications
0
10
0
Order By: Relevance
“…Parsimonious solutions used by insects exist for many other tasks that are relevant to robotics. These include optic flow-based visual navigation for obstacle avoidance (48,72,(110)(111)(112), target following (113), altitude control (114,115), and landing (116). For many of these tasks, the main principles are known, but the exact mechanisms that should be implemented in robots are an area of active research.…”
Section: Parsimonymentioning
confidence: 99%
“…Parsimonious solutions used by insects exist for many other tasks that are relevant to robotics. These include optic flow-based visual navigation for obstacle avoidance (48,72,(110)(111)(112), target following (113), altitude control (114,115), and landing (116). For many of these tasks, the main principles are known, but the exact mechanisms that should be implemented in robots are an area of active research.…”
Section: Parsimonymentioning
confidence: 99%
“…In hoverflies [35] and dragonflies [36], a pursuer matches its relative position and speed to that of the target individual such that its projected image on the target's retina is relatively invariant, and so the optic flow is similar to that created by the background. The algorithms that an insect might use to achieve this have, more recently, been applied to control systems for missiles and ships that seek to intercept a target whilst minimising their own detectability [8,37,38] (Figure 3).…”
Section: Minimising the Signalmentioning
confidence: 99%
“…As experimental studies have shown that desert ants can use either of these sensory modes, it was proposed here to test all the possibilities involving these cues. The optic flow has long been used for odometric cues estimation [61,62] as well as obstacle avoidance [63,64,65] or object tracking [66]. Multiple strategies have been proposed and mostly make use of high-resolution cameras 5 .…”
Section: Toward Navigation Skills: the Odometric Cuesmentioning
confidence: 99%